STUDI PENENTUAN NILAI MARKUP MINIMUM SEBAGAI STRATEGI UNTUK MEMENANGKAN PENAWARAN PROYEK KOSNTRUKSI DENGAN MODEL FAIR AND REASONABLE MARKUP (FARM) - Sudarsana, Dewa Ketut; Dharma Warsika, Putu; Jaya Surya Dharma, I G. N. (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011, 2012)
The rapidly growing in the development of construction project in Indonesia has brought a very powerful impact in the construction business. The rise of the development of construction business has led to tight competition for contractors to win the tender. A model of Fair and Reasonable Markup (FARM) by Farid and Boyer in 1985 is used to determine the smallest markup value / minimum bid price that used by contractors to meet the return on investment / capital which is expected in the project. By using FARM models, contractors are expected to determine a price that is competitive, but it still can generate sufficient profits for the contractors as bidders. The study results in markup values ranging from 1.58% to 1.69% and the rate of return on investment expected by the contractor is about 20% per year.
Keywords: Tender, competitive, profit margin, FARM